Another empirical look at the Kuznets curve - Rabindra Bhandari; Gyan Pradhan; Mukti Upadhyay (International Journal of Economic Sciences and Applied Research, 2010)
This paper examines the functional relationships between income inequality, economic factors, institutions, and Kuznets' inverted-U hypothesis. A model that incorporates interactive as well as direct effects of several factors to capture their combined effect on inequality is developed. The model is estimated using two popular measures of inequalitythe Gini coefficient, and the ratio of income shares in income distributionusing a panel data set for 57 countries from 1987 to 2006. The results provide support for Kuznets' hypothesis; however, the relationship between growth and inequality is conditioned by a host of economic and institutional factors.
Keywords: O1; O40; 330; Kuznets curve; inequality; growth; Gini coefficient; income shares